Benchmarking the knowledge management practices of construction firms - Kale, Serdar; Karaman, A. Erkan (Journal of Civil Engineering and Management, 2012)
Knowledge management is rapidly becoming a key organizational capability for creating competitive advantage in the construction industry. The emergence of knowledge management in this capacity poses enormous challenges to executives of construction firms. This paper proposes a model for benchmarking those knowledge management practices of AEC firms that can guide and assist construction business executives in meeting these challenges. The proposed model incorporates benchmarking and knowledge management concepts with importance-performance analysis (IPA) maps. It is a simple visual tool that can provide powerful diagnostic information to executives of AEC firms by evaluating their firm’s knowledge management practices, identifying their firm’s comparative advantages and disadvantages with regard to each knowledge management practice, and setting priorities for managerial actions related to knowledge management practices that need improvement. A real-world case study is presented to illustrate the implementation and utility of the proposed model.